1979
DOI: 10.1029/jb084ib09p04592
|View full text |Cite
|
Sign up to set email alerts
|

Plane shock wave studies of porous geologic media

Abstract: Plane shock wave experiments have been conducted on two highly porous rocks, Mount Helen tuff and Indiana limestone, in both dry and water-saturated states up to stress levels of about 4 GPa. A light-gas gun was used to load the sample in uniaxial strain, and the subsequent wave motion was monitored with particle-velocity gages. All four materials studied show evidence of time-dependent behavior. The timedependent behavior in the highly porous dry rocks is associated with the closing of pores. The strong time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…We speculate that this penetration equation will be reasonably accurate for larger scale projectiles, but data from much more expensive field tests must be obtained to confirm our speculation. (Ortiz, 1966;Carnacho and Ortiz, 1997 (Fossum, Senseny, Pfeifle, and Mellegard, 1995), (2) split Hopkinson bar experiments (Green and Perkins, 1968;Lindholm, Yeakley, and Nagy, 1974;and Lipkin, Grady, and Campbell, 1977), (3) plane shock wave studies (Larson and Anderson, 1979), (4) dynamic tensile failure with planar-impact techniques (Grady and Hollenbach, 1979;Ahrens and Rubin, 1993), and (5) compression-shear loading with plate impact experiments (Aidun and Gupta, 1995). Data from other experimental techniques may also be required for a careful target analysis.…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that this penetration equation will be reasonably accurate for larger scale projectiles, but data from much more expensive field tests must be obtained to confirm our speculation. (Ortiz, 1966;Carnacho and Ortiz, 1997 (Fossum, Senseny, Pfeifle, and Mellegard, 1995), (2) split Hopkinson bar experiments (Green and Perkins, 1968;Lindholm, Yeakley, and Nagy, 1974;and Lipkin, Grady, and Campbell, 1977), (3) plane shock wave studies (Larson and Anderson, 1979), (4) dynamic tensile failure with planar-impact techniques (Grady and Hollenbach, 1979;Ahrens and Rubin, 1993), and (5) compression-shear loading with plate impact experiments (Aidun and Gupta, 1995). Data from other experimental techniques may also be required for a careful target analysis.…”
Section: Introductionmentioning
confidence: 99%
“…As a validation test, all of the parameters determined to this point (see Table 1) are used to predict the plate-slap, plane shock-wave experiments of Larson and Anderson [13] on Salem Limestone that provide uniaxial-strain data at extremely high strain rates on the order of 10 5 -10 7 s -1 . Figure 13 shows the results for uniaxial strain simulations made at strain rates of 10 5 , 10 6 , 10 7 , and 10 -5 s -1 (the experimental quasi-static uniaxial-strain results conducted at 10 -5 s -1 are included for comparison).…”
Section: Dynamic Resultsmentioning
confidence: 99%
“…The particle velocity experimental design is similar to those of Grady et al [1974], Larson and Anderson [1979], and Kondo et al [1980] and makes use of electromagnetic particle velocity gauges [Dremin and Shvedov, 1974].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Similar experiments were conducted on polycrystalline quartz and perthitic feldspar by Grady et al [1975] and Grady and Murri [1976], who used manganin stress gauges to determine Hugoniot sound velocities and found that these rocks lose shear strength when shocked to pressures above 20 GPa. Larson and Anderson [1979] used particle velocity gauges to study limestone and tuff at lower stress levels (4 GPa) and attributed the observed time-dependent behavior to the closing of pores in these rocks.…”
Section: Introductionmentioning
confidence: 99%